The Non-Stationary Thermal Mode for Barrier Building Constructions in Non-Symmetric Boundary Conditions - Borshch, Olena; Borshch, Volodymyr; Guzyk, Dmytro (International Journal of Engineering and Technology, 2018)
In barrier building constructions the heat transfer occurs both at the expense of thermal conductivity and as a result of liquid and air vapors resistance. The mechanism of such resistance differs from classical processes of diffusion and the laws of hydrodynamics for integral medium.The temperature mode of the surface and deep layers of barrier building constructions in non-symmetric boundary conditions wasÂ Â Â Â analyzed. A mathematical model was developed that characterizes the change in the thermal state of barrier constructions during thermal diffusion. The method for calculating the non-stationary thermal modes of flat walls was presented.Â Â